An experimental and numerical study of reinforced conventional concrete and ultra-high performance concrete columns under lateral impact loads. (15th December 2019) - Wei, Jie; Li, Jun; Wu, Chengqing
Highlights: Axially loaded UHPC and RC columns were tested under lateral impact loads. Impact response of UHPC columns was studied through numerical modelling. Analytical damage assessment was proposed for UHPC columns. Abstract: This paper presents an experimental and numerical study on the dynamic behaviour of axially-loaded reinforced conventional concrete (RC) and ultra-high performance concrete (UHPC) columns against low-velocity impact loading. The test specimens were divided into two groups with square and circular cross-section shapes, and each group includes both RC and UHPC columns. The impact scenario was modelled with a drop weight falling freely on the column mid-span. Brittle failure with shear plug formation was observed in RC columns while UHPC columns remained a flexure response with minimal damage under severe impact loads. To further interpret the experimental data, detailed finite element (FE) models were developed for RC and UHPC columns. A Continuous Surface Cap Model (CSCM) which accounts for the triaxial material strength, post peak softening and strain rate effect was adopted for UHPC material. After validating the material and structural model based on the testing data, extensive numerical simulations were performed to predict the UHPC column residual loading capacity after lateral impacts. Impact mass-velocity (M-V) diagrams were derived for the UHPC column damage assessment, and analytical formulae which could be easily applied to generate M-V diagrams were derived based on parametric studies.